Improving the Quality of Local Coffee through Production Management in Kare Village, Madiun, East Java - Sayekti, Cenuk; Hariyono, Hariyono; Wijoyo, Suparto (Jurnal Abdimas, 2024)
Coffee serves as a vital agricultural product in Madiun Regency, particularly flourishing on the slopes of Mount Wilis in the Kare District. Presently, approximately 55 hectares of land in this region are dedicated to coffee cultivation, primarily managed by a local farmer group. The predominant variety cultivated in Kare is high-quality robusta, which thrives at an elevation of 700 meters above sea level, making it particularly well-suited for this type of coffee. Known locally as Kare coffee or Wilis coffee, this product is distinctive due to its unique flavor profile, which sets it apart from other Indonesian coffees, as it is exclusively sourced from the slopes of Mount Wilis. All coffee sold under this label is cultivated and processed by the Mugi Lestari farmer group, which faces significant competition in the local and national coffee markets, prompting them to seek broader marketing opportunities. However, the increasing demand for coffee necessitates that farmers in Kare Village enhance their skills in production management to ensure that their coffee not only improves their livelihoods but also empowers them economically. The challenges encountered by these farmers include a lack of understanding regarding the significance of effective production management for enhancing product competitiveness and the absence of training or support to bolster their human resource capabilities. Additionally, the low wages and income levels of coffee farmers in Kare Village hinder their ability to address these issues independently, underscoring the need for targeted assistance and training in coffee production management. In response to these challenges, the Community Service Team proposes a comprehensive solution that includes socialization, counseling, and support focused on the effective management of Kare Coffee production